A Review of Structural Performance of Oil Palm Empty Fruit Bunch Fiber in Polymer Composites - Reza Mahjoub; Jamaludin Bin Mohamad Yatim; Abdul Rahman Mohd Sam (Advances in Materials Science and Engineering)
According to environmental concerns and financial problems, natural fibers have become interesting and fascinating nowadays to be used as an industrial material and structural material for rehabilitating of structures. Oil palm empty fruit bunch fiber (OPF) is a natural fiber which is found a lot in tropical areas. Scientists have used OPF fiber with many types of resins such as epoxy, polypropylene, polyester, and phenol formaldehyde. Therefore, this paper focused on the properties of OPF fiber and gathered mechanical properties of OPF composites (OPF as reinforcement of polymer) reported by other researchers in terms of tensile and flexural properties. Furthermore, the chemical surface modification methods to solve the interfacial bonding of fiber and polymer were mentioned. In addition, the results of hybrid composites of OPF were also discussed in this paper. Meanwhile, the results of composites were compared to pure resin properties and also the stress-strain diagram and internal strain energy of composites were considered. Besides, the effects of adding OPF to other composites to make a new hybrid composite were indicated. Finally, it is clear that the use of oil palm fiber composites for structural elements for bearing loads is not recommended but the usage of OPF composites for secondary structural elements may be recommended due to future researches.